ENT600: Smart swimsuit / Aina Zahirah Zaki … [et al.] - Zaki, Aina Zahirah; Aziz, Airin Fatehah; Roslan, Nurul Azra; Yahaya, Nurul Suryanie; Abd Latif, Siti Zarifah (2018)
After initial observation towards available swimsuits at the market, the team had come out with an idea on a product. The innovation is a SMART-swimming suit. The SMART swimsuit is an innovation that has swim assist technology to control floating ability. This product come with specialty in the ability to move the muscle by using functional electrical stimulation (FES) pads to assist movements for swimming and subsequently providing balance for body to float. This swimming suit also equipped with switch on and off to initiate and stop the functionality of the FES.